The Influence of PMH Screening Training on Postpartum Mothers on the Knowledge, Attitude, and Practice of Midwives - Ana Pujianti Harahap; Mateus Sakundarno Adi; Ayun Sriatmi; Cahya Tri Purnami (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Perinatal Mental Health (PMH) can impact both the mother and her baby, leading to a decrease in quality of life, premature delivery, reduced oxytocin levels, developmental disorders in the baby, and incidents of suicide. WHO recommends that PMH screening for postpartum mothers conducted by trained healthcare professionals can reduce the impact caused by PMH. The aim of this study is to analyze the effectiveness of training in improving the knowledge, attitudes, and practices of midwives regarding the implementation of Perinatal Mental Health (PMH) screening for postpartum mothers. Methods: The research method used is quantitative with a quasi-experimental pre-posttest control group design to evaluate the knowledge, attitudes, and skills of midwives in conducting Perinatal Mental Health (PMH) screening for postpartum mothers. A total of 60 midwives were sampled and divided into 2 (two) groups, with 30 midwives in each group, the control group and the intervention group. Results: The research results show that the training successfully significantly increased the midwives' knowledge (p-value 0.000). However, the training did not have a significant impact on attitude changes (p-value 0.137) and midwife practices (p-value 0.068). Conclusion:The training provided successfully increased midwives' knowledge regarding perinatal mental health screening, but it has not yet significantly changed their attitudes and practices. This is likely due to the training duration being too short and the evaluation time being insufficient to support sustainable change.